MODEL TINGKAT SIGNIFIKANSI UNTUK MENGETAHUI FAKTOR-FAKTOR KINERJA DENGAN KEPUASAN KERJA SEBAGAI MEDIASI - Eddi Indro Asmoro (Jurnal Ilmiah Dinamika Teknik, 2014)
Appointment of performance values refer to the value of job satisfaction as the mediation is very important, this is due to that the value of job satisfaction as the basis for a decision can. Policy in the form of a decision must know prioritasdari scale level factors that influence job satisfaction. Job satisfaction is placed here as the value of mediation to justify the value of the performance, because the nature of the character of the individual 'job satisfaction that can be used as an objective assessment of the condition of performance evaluation system with feedback method (top-down and button-up).Factors to determine the significance level of performance and job satisfaction as the mediation conducted empirical methods. A review of the empirical method here, divided into dimensions that are operationally used as an indicator to make beads statement. Research methods using multiple regression-correlation, where the regression method to determine whether there is influence and correlation methods to determine how the level of influence.This study was limited to designing the model determines construct the significance of factors that affect the performance and job satisfaction as the mediation. It is expected to facilitate further research on the development of performance evaluation system for the organization.Key words:Factors, performance, mediation, job satisfaction